حجية خبر الآحاد فيما تعم به البلوى - عاشور, آدم; دريش, سيف الدين; نعجة, فؤاد (University of Eloued-جامعة الوادي, 2019)
تعتبر مسألة الاحتجاج بخبر الآحاد الوارد فيما تعم به البلوى؛ مظهر اهتمام عند الأصوليين ، فلا تكاد تنظر الى مؤلف أصولي إلا وتجده يتطرق إلى هذا الموضوع، وهذا في الغالب الأعم. وللأهمية بمكان قمنا ببحث في هذا الباب موسوم بحجية خبر الآحاد فيما تعم به البلوى نطرح في هذا الاخير الاشكالية الآتية :ماهي مذاهب العلماء في الاحتجاج بخبر الآحاد فيما تعم به البلوى مبرزين هدفين لهذه الدراسة، بيان أدلة مذاهب العلماء في الاحتجاج بخبر الآحاد فيما تعم به البلوى مع إيراد بعض المسائل الفقهية التطبيقية المبنية على الخلاف فيها متبعين في تحقيق ذلك خطة لثلاثة مباحث Research Summary The issue of protesting the news of the one contained in the generalization of Balwa is a manifestation of interest among the fundamentalists, and it is hardly possible to look at the author of fundamentalism except to find him addressing this subject, and this is most often the case . It is important that we have examined this section is characterized by the authority of the news of atheism in the midst of Balwa, we raise the following problematic in the latter : What are the doctrines of scientists in protest the news of atheism, With the introduction of some practical jurisprudence based on the dispute in the follow-up in the realization of this plan for three aspects - the news of the atheist - all Balawi - the author of the news of atheism in what is widespread Balwa, and finally concluded several results of the most important that the news of the individual contained in the whole Balawi legitimacy argument When the public is different to the h Faithful as it is a great asset in jurisprudence graduating on the dispute in which many sub - issues in this case , we recommend studying the general relationship with the scourge of fundamentalism and the rules of jurisprudence independent research, and make the effort to find emerging applications as permeated by contemporary scourge. -
مذكرة ماستر
Keywords: حجية /خبر الاحاد /البلوى; Authentique / actualité des uns / calamité